Student Interests In Investing In The Capital Market - Margareta, Fika (Utami Publisher, 2024)
The aim of this research is to determine students' interest in investors in the capital market by using a literature study research method by reviewing and analyzing several journals and books that are closely related to student interest in investing in the capital market. The results of the analysis from various literature will be used as references and learning resources in explaining material regarding Student Interest in Investing in the Capital Market, so that writers and readers can clearly understand Student Interest in Investing in the Capital Market. The results of this research will later be used to provide and clarify insight into students' interest in investing in the capital market.